ABOUT THE ESSENCE AND CONTENT OF MOTIVATION OF NEW MEMBERS OF A PROFESSIONAL GROUP: THE THEORETICAL REVIEW - Valentyna V. Pashchenko (Alfred Nobel University Publisher, 2021)
The concept of motivation is considered as a process of complex influence on personality behavior in order to achieve the set goals. It was established that the promising direction of motivation of new members of the professional group is the organization and development of teamwork and the formation of teamtargeted motivation. In this regard, the content of the definitions of the team, team work, professional group is disclosed, based on the analysis in which the main stages of team development are revealed. The prerequisites for effective teamwork are defined. Motivation as a driving force and one of the priority functions of management is considered. It is proved that peculiarities of professional group development determine ways and directions of motivation of its members. The peculiarities of the motivational process of the team were clarified and the problem of the ratio of motivation and goals was revealed. A generalized understanding of the phenomenon of synergistic effect, which consists in increasing the efficiency of activities as a result of integration, is presented. The main theories of motivation in groups are analyzed: meaningful theories of motivation, which are based on the identification of internal motives that force a person to act like this and not otherwise (twofactor theory by F. Herzberg, theory of acquired needs by D. Mack Clelland, theory of Maslow hierarchy of needs, theory of needs by ERG K. Alderfer) and procedural theories that analyze people's behavior regarding the distribution of effort to achieve different goals and choose a specific type of behavior aimed at meeting needs (justice theory by J. Adams, expectation theory by V. Vrum, Porter-Lawler model, theory X, Y D. McGregor, theory Z (participative management) by V. Ouchi).